Evaluation of the effectiveness of combination therapy for post-occlusive retinal changes - A.G. Shchuko; S.I. Zhukova; M.V. Akulenko (Офтальмохирургия)
Purpose. To evaluate the volume of therapeutic measures necessary for the relief of macular edema in patients with Branch Retinal Vein Occlusion (BRVO) depending on the initial macular ischemia. Material and methods. 142 patients with macular edema on the background of BRVO were included in the study. All patients received intravitreal injection of ranibizumab in 1+PRN regimen, laser coagulation if necessary. Allpatients underwent examination, including visometry, electroretinography, optical coherence tomography (OCT) and OCT angiography. The number of injections and laser manipulations over the entire follow up period was taken into account. The comparative analysis of the obtained results was carried out in 3 groups formed depending on the area of the initial macular ischemia. The significance level was p<0.0125. Results. It was found that in group 1 patients with an initial area of macular ischemia from 0.3 to 1.5 mm2, 1.5±0.7 injections of ranibizumab were required to resorb macular edema and increase visual acuity by more than 2 times. In group 2 patients with an area of macular ischemia from 1.5 to 1.8 mm2, an average of 7.2±2.2 injections of ranibizumab were required to relieve macular edema, in 62% of cases, sectoral laser coagulation, in 15% – panretinal laser coagulation of the retina, while visual acuity improved unreliably (p>0.05). In group 3 patients with an initial area of macular ischemia more than 1.8 mm2, despite an average of 3.6±1.4 injections of ranibizumab and in 58% of cases of panretinal laser coagulation, visual acuity did not significantly change (p>0.05), and the area of capillary nonperfusion increased in the perifoveal zone and on the periphery of the retina. Conclusion. The volume of therapeutic measures in patients with macular edema on the background of BRVO and the possibility of improving visual functions depends not only on the degree of ischemia of the peripheral retina, but also on the initial area of ischemia of the macular zone according to OCT angiography, the amplitude of the b-wave ERG and oscillatory potentials, which can be considered as markers that allow predicting the effectiveness of combined therapy of post-occlusive retinal changes.